Legal Regulation of the Occupational Health and Safety in the Non – Standard Work in The Slovak Republic - Seilerová, Monika (Wydział Prawa i Administracji Uniwersytetu Rzeszowskiego, 2018)
As it is typical for the current world of work, employees often perform dependent work in forms that are not standard. They are characterized by the specificities of the legislation, including working conditions. When using the term non-standard work, we follow the definition of the International Labour Organization. For the purpose of this paper, we may regard especially these forms: work from home, teleworking, temporary agency work and work performed on the basis of contracts for work performed outside the employment relationship as an institute typical for Slovak (but also Czech) labour law. The aim of the paper is to analyze the legal regulations on health and safety at work in the Slovak Republic, in the context of the mentioned forms of dependent work. We will attempt to investigate the effectiveness of the current legal regulation, including some theoretical and application problems. We will also focus on assessing the impact of non-standard work on the physical and mental health of employees and on the possibilities of managing the factors of this work by the employer.

Ponieważ jest to typowe dla obecnego świata pracy, pracownicy często wykonują prace zależne w formach, które nie są standardowe. Charakteryzują się one specyfiką przepisów, w tym warunkami pracy. Używając terminu "praca niestandardowa", kierujemy się definicją Międzynarodowej Organizacji Pracy. Na potrzeby niniejszego dokumentu możemy szczególnie uwzględnić następujące formy: praca w domu, telepraca, praca tymczasowa i praca wykonywana na podstawie umów o pracę wykonywanych poza stosunkiem pracy jako instytucja typowa dla pracy słowackiej (ale także czeskiej) prawo. Celem niniejszego artykułu jest analiza przepisów prawnych dotyczących bezpieczeństwa i higieny pracy w Republice Słowackiej w kontekście tych form pracy zależnej. Postaramy się zbadać skuteczność obecnej regulacji prawnej, w tym niektóre problemy teoretyczne i aplikacyjne. Skupimy się również na ocenie wpływu niestandardowych prac na zdrowie fizyczne i psychiczne pracowników oraz na możliwościach zarządzania czynnikami tej pracy przez pracodawcę.
Ustawodawstwo zdrowia i bezpieczeństwa zawodowego w niestandardowych pracach w Republice Słowackiej
Keywords: non – standard work; teleworking; occupational health and safety; physical health; mental health; niestandardowa praca; telepraca; bezpieczeństwo i higiena pracy; zdrowie fizyczne; zdrowie psychiczne